Mikrocytární a hypochromní anémie - Chrobák, L (Vnitrni lekarstvi, 2001)
In the majority of cases, microcytosis is the result of impaired hemoglobin synthesis. Disorders of iron metabolism and protoporphyrin and heme synthesis, as well as impaired globin synthesis, lead to defective hemoglobin production and to the generation of microcytosis and microcytic anemia. Iron deficiency anemie, anemia of chronic diseases, thalassemias, congenital sideroblastic anemias and homozygous HbE disease are the main representatives of microcytosis and microcytic anemias. Serum iron, total iron binding capacity, transferrin saturation, serum ferritin, serum transferrin receptor, transferrin receptor-ferritin index, and zinc-protoporhyrin concentration in erythrocytes are tests used for assessment of iron deficiency. The convention laboratory test for diagnosing iron deficiency is the measurement of serum ferritin. The most precise method for evaluating body iron stores is the examination for iron on aspirated bone marrow or marrow biopsy. Increased content of Hb A2 over 3.5% is diagnostic for beta-thalassemia. Presence of ringed sideroblasts is characteristic of sideroblastic anemias. Hemoglobin electrophoresis is required for the diagnosis of hemoglobinopathy E. The optimal therapeutic regimen in iron deficiency anemia used in this country is to administer 100 mg of elemental iron twice daily separately from meals. Ferrous sulphate (Ferronat Retard tbl. or Sorbifer Dulures tbl.) which are slow-releasing iron formulations are preferred because of their low cost, high bioavailability and low side-effects. Parenteral iron therapy is justified only in patients who cannot absorb iron, who have blood losses that exceed the maximal absorptive capacity of their intestinal tract or who are totally intolerant of oral iron. However, parenteral iron therapy may be associated with serious and even fatal side-effects.
Keywords: talasemie; Anemia, Hypochromic; Anemia, Iron-Deficiency; Humans; diferenciální diagnóza; Thalassemia; Diagnosis, Differential; lidé; anemie z nedostatku železa; hypochromní anemie